ANALISIS PROSES BISNIS PENGADAAN JASA DENGAN PENDEKATAN QEF, RCA, DAN BPI - Anindita Araya Prigara; Yugowati Praharsi; Gaguk Suhardjito (Proceeding Maritime Business Management Conference, 2022)
The largest shipbuilding company in Indonesia has a business in the development and design capabilities of Warships and Commercial Ships; construction and maintenance, repair and Overhaul (MRO) of Submarines, Warships, Commercial Ships; and maritime products such as General Engineering, energy and electrification products, and Technology Development. It has several divisions, one of which is the supply chain division. The business processes applied to the supply chain division is service procurement department for the ship maintenance and repair business which are still running less effectively. The problem that is often experienced in this business process is the mismatch between the business process flowchart and the reality on the ground which causes delays in the issuance of service procurement contracts. To analyze the service procurement process in the ship maintenance and repair business, this study uses the Quality Evaluation Framework (QEF) method. From the results of quality factors that are still not in accordance with the company's target, a root cause will be carried out using Root Cause Analysis (RCA), namely fishbone analysis. After finding the root of the problem, this research produces a proposal for improving business processes using Business Process Improvement (BPI). The results of the business process analysis of the issuance of service procurement contracts resulted in the calculation of three quality factors that did not match the target and realization, the three quality factors were Resource Efficiency of 90%, Availableness of 50%, and Cycle Time of 29 days.